Investigating the Causes of Spectacle Non-Tolerance in Patients at a Tertiary Eye Hospital in Nepal - Mukherjee, Tinku; Sah , Sanjay Kumar; Sah , Sushil Kumar; Adhikari, Pankaj Ray; Kumar Patel, Pradeep (Journal of Ophthalmic and Optometric Sciences, 2024)
Purpose: To find out the causes of the non-tolerance of spectacles used among the patients visiting Biratnagar Eye Hospital, Nepal. Patients and Methods: This prospective cross-sectional study was conducted among patients visiting the optical department of Biratnagar Eye Hospital, Biratnagar, Nepal. Patients of age more than 20 years who fall under the definition of spectacle non-tolerance were included. Patients’ spectacle intolerance was verified based on the tolerance limit criteria by the American National Standards Institute (ANSI Z80.1-2015). Results: A total of 8,000 spectacles were prescribed during the 3 months of study period between April to June 2022. Among these prescriptions non-tolerance cases accounted for 104 patients. The mean age of patients was 41.63 ±13.30 year, ranging between 20 and 70 years. From the total population, 61.55% were male. The prevalence of spectacle non-tolerance was 1.3%. The majority of non-tolerance occurred in the 41-50 age group (31.0%). A major cause of non-tolerance to spectacles was dispensing error accounting for 48% of cases, particularly notable among bifocal lens users. Conclusion: It is crucial to exercise careful consideration when prescribing and providing glasses to patients. Practitioners should eliminate transcription errors completely, as they are unacceptable from a professional standpoint. Opticians should diligently verify all essential parameters for glasses and ensure proper alignment both on and off the face. This meticulous approach serves to reduce intolerance and elevate patient satisfaction with their spectacles.